(SFSLVXJORPLMJ FUFYPAs - (SIga(Szflursrynrw M}vxga(Sws; (S\ga(Suury Ogac(Sega (SMs ((SXys}kjx}(B,s, 2001)
(SOFKRERNRDLMFV SURVFDDLVFLV J MRLP]PLMJ FUFYPA MAL XR SURBNJOA OFXUJVJV X]P SAUAXJUJVF]P XF[PLMFV FNFD[RY FU]XJOAXRNRDLRY(B, (SVXAXLVXLMJ XRY EFLDOAXRV MAL APANYVJ XRY EFLDOAXRVs
(SOFKRERNRDLMFV SURVFDDLVFLV J MRLP]PLMJ FUFYPA MAL XR SURBNJOA OFXUJVJV X]P SAUAXJUJVF]P XF[PLMFV FNFD[RY FU]XJOAXRNRDLRY(B, (SVXAXLVXLMJ XRY EFLDOAXRV MAL APANYVJ XRY EFLDOAXRVs